Un tabú en la sociedad grecorromana: la mujer y el vino - Real Torres, Carolina (1995)
Women in Antiquity were valued through their fertility. Thus, the fact that their destiny as wives was determined by their capacity of providing legitimate descendants causes a series of biological, social and ethical factors which ruled their body. This paper is an attempt to draw a reasonable explanation of some features of the behaviour of women in society. It also gives an account of the various kinds of restrictions imposed on them.
Keywords: Mujeres; Problemas sociales; Vinos